Non-Linear Estimates of the Engel Curves - Prais, S. J. (Review of Economic Studies, 1952)
Journal Article Non-Linear Estimates of the Engel Curves Get access S. J. Prais S. J. Prais Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 20, Issue 2, 1952, Pages 87–104, https://doi.org/10.2307/2295843 Published: 01 January 1952